Childcare Correlates of Physical Activity, Sedentary Behavior, and Adiposity in Preschool Children: A Cross-Sectional Analysis of the SPLASHY Study. (11th November 2018) - Arhab, Amar; Messerli-Bürgy, Nadine; Kakebeeke, Tanja H.; Lanzi, Stefano; Stülb, Kerstin; Zysset, Annina E.; Leeger-Aschmann, Claudia S.; Schmutz, Einat A.; Meyer, Andrea H.; Munsch, Simone; Kriemler, Susi; Jenni, Oskar G.; et al.
Abstract : Background . The childcare (CC) environment can influence young children's physical activity (PA), sedentary behavior (SB), and adiposity. The aim of the study was to identify a broad range of CC correlates of PA, SB, and adiposity in a large sample of preschoolers. Methods . 476 preschool children (mean age 3.9 yrs; 47% girls) participated in the Swiss Preschoolers' Health Study (SPLASHY). PA and SB were measured by accelerometry. Outcome measures included total PA (TPA), moderate-to-vigorous PA (MVPA), SB, body mass index (BMI), and skinfold thickness (SF). PA measures consisted of both daily PA during CC attendance days and overall daily PA (CC and non-CC days). Results . We identified the following CC correlates for higher TPA and/or higher MVPA or lower SB during CC attendance days: older age, sex (boys), more frequent child-initiated interactions during CC, mixing different ages within a group, and the presence of a written PA policy in the CC (allp ≤ 0.02 ). The CC correlates for overall TPA and/or MVPA or lower overall SB including both CC and non-CC days were the following: older age, sex (boys), more frequent child-initiated interactions during CC, mixing different ages within a group, less parental PA involvement in the CC, and having a larger surface area in CC (allp ≤ 0.046 ). Correlates for lower SF were sex (boys) and parental PA involvement in the CC (allp ≤ 0.02 ), and, for lower BMI, only increased age (p = 0.001 ) was a correlate. Conclusions . More frequent child-initiated interactions and mixing different ages in CC, the presence of a written PA policy, and a larger CC surface are correlates of PA and SB during CC attendance days and/or of overall PA. Parental involvement in CC PA projects was a correlate for reduced body fat. These novel factors are mostly modifiable and can be tackled/addressed in future interventions.